Calorie adequacy for optimal cognitive recovery among hospitalised traumatic brain injury patients - Mohd Ibrahim bin Abdullah
Cognitive impairment is a common problem after traumatic brain injury (TBI). In addition to the healing process of physical injury and prevention of malnutrition, the ideal dietary recommendation is crucial for favourable cognitive outcomes. However, to date, it is less clear on the amount of calorie for optimal cognitive recovery among TBI patients. Therefore, this research aimed to determine adequate calorie for optimal cognitive recovery among hospitalized TBI patients. This research was conducted in two phases which were Phase 1 (Observational study) to determine the association between calorie intake and cognitive function and Phase 2 (Intervention study) to determine the effect of a hypocaloric diet on cognitive function among mild TBI patients. The TBI patients (Phase 1; n=60, and Phase 2; n=26) from the neurosurgery ward of Hospital Sultanah Nur Zahirah who met the criteria were enrolled in this study. Patients were interviewed using 24-hour diet recall and cross-checked with a self administered food diary and later were analysed for determination of calorie intake. Progression of clinical parameters such as vital signs, associated symptoms, number of wounds, bedsore and length of stay were noted in clinical assessment using available hospital records. Whereas, cognitive function was evaluated by neuropsychology test (Montreal Cognitive Assessment and Digit Symbol Coding test) and neurophysiology test (electroencephalography). Findings from Phase 1 demonstrated a significant association between calorie intake and cognitive function for both high and low calorie intake groups with better cognitive improvement was exhibited in the latter group. The findings also suggested that calorie intake of 55% from calculated calorie requirement was optimal for cognitive recovery as proven by the ROC curve (AUC=0.684, S =0.004, 95%CI=0.597-0.770) and fit model equation. Whilst, findings from Phase 2 confirmed that the provision of a hypocaloric diet (50-60% of calculated calorie requirement) showed significant cognitive improvement compared to a normocaloric diet (80-100% of calculated calorie requirement) among mild TBI patients (p<0.05). Besides, the risk of obtaining poorer cognitive function was reduced by 66.7% among hypocaloric diet relative to the normocaloric diet group (risk ratio 0.333 [95%CI 0.040- 2.801]) using risk estimation test. More interestingly, all clinical outcomes and weight changes were not compromised even though with the provision of a hypocaloric diet. Both Phase 1 and 2 showed that cognitive improvement was inversely associated with the power ratio of slow to fast brain frequency bands, with the slow frequency bands were dominant across electrodes during the first visit and vice versa fast frequency bands during the follow-up visit. In conclusion, hypocaloric diet (50-60% of calculated calorie requirement) exhibited better cognitive recovery compared to a normocaloric diet (80-100% of calculated calorie requirement) without compromising clinical outcomes or imposing risk of malnutrition among mild TBI patients. This study provides a novel approach in the dietary recommendation for TBI patients which produces a beneficial impact on cognitive rehabilitation and this preferable outcome will certainly improve their post-injury quality of life.